2018
DOI: 10.1093/pm/pny088
|View full text |Cite|
|
Sign up to set email alerts
|

The Intersections of Chronic Noncancer Pain: Culturally Diverse Perspectives on Disease Burden

Abstract: Health care providers must consider how the intersectionality of social identities related to ethnoculture, social class, migration status, and gender can factor into the creation and maintenance of chronic pain disparities. A greater, more thoughtful incorporation of intersectionality in chronic pain research and clinical practice will ensure that pain management approaches are designed and applied in a way that reflects the social context of affected communities and individuals from those communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…This study utilised a paper version of the PRISM+ [11], laminated to allow disks to be moved and positioned easily by patients. The original paper version was selected over electronic versions as our experience with CALD communities in South West Sydney Local Health District (SWSLHD) indicated high rates of social disadvantage and limited familiarity with technology in health [30]. Further, the paper versions allowed for translations to be readily printed and taken home by participants for repeat testing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study utilised a paper version of the PRISM+ [11], laminated to allow disks to be moved and positioned easily by patients. The original paper version was selected over electronic versions as our experience with CALD communities in South West Sydney Local Health District (SWSLHD) indicated high rates of social disadvantage and limited familiarity with technology in health [30]. Further, the paper versions allowed for translations to be readily printed and taken home by participants for repeat testing.…”
Section: Methodsmentioning
confidence: 99%
“…For the PRISM+, the additional disks selected were informed by research involving Assyrian, Arabic and Vietnamese communities from SWSLHD [6, 30], and previous use of the PRISM+ in chronic pain settings [12]. Previous qualitative research findings from each CALD community emphasised the importance of family, fulfilling traditional occupational roles, social relationships, and spirituality, on the experience of pain and construction of ethnocultural identity [6].…”
Section: Methodsmentioning
confidence: 99%
“… 4 , 5 Given that chronic pain is a complex and multidimensional experience whose assessment, study, and management are influenced by a variety of biopsychosocial contexts, 6 it is not surprising that a variety of studies have found that patients’ socioeconomic status (SES) can affect their experiences, treatments, and health outcomes. 7–9 Patients’ chronic pain experiences have been shown to be affected by factors such as their gender, ethnicity, social class, income, education, and the neighborhood in which they reside. 7 , 9–11 The Canadian Pain Task Force 12 agrees that such factors play a role in explaining the inconsistent and inequitable experience of pain and access to pain care in Canada.…”
Section: Introductionmentioning
confidence: 99%
“… 7–9 Patients’ chronic pain experiences have been shown to be affected by factors such as their gender, ethnicity, social class, income, education, and the neighborhood in which they reside. 7 , 9–11 The Canadian Pain Task Force 12 agrees that such factors play a role in explaining the inconsistent and inequitable experience of pain and access to pain care in Canada. Therefore, among the six recommendations that the Canadian Pain Task Force has suggested to the Canadian federal government to improve the prevention and management of chronic pain are those specifically related to improving both equitable access to pain care and ensuring “equitable approaches for populations disproportionately impacted by pain.” 12 (p1)…”
Section: Introductionmentioning
confidence: 99%
“…Such pain behaviours may include, facial expressions, vocalisations, changes in body positioning (limping, posturing or guarding), changes in normal behaviour (withdrawal from socialisation), or changes in physiological signs (sweating, pallor) (Achterberg et al, 2013).These behaviours may be indicators to an observer, of the presence of pain and the only way that a person with dementia, other neurological or sensory deficits, can communicate with others that something is wrong (Keefe et al, 2011). However, these behaviours may also be altered or absent in people with persistent pain, or people from different social or CALD backgrounds (Brady, Veljanova, & Chipchase, 2019;Dansie & Turk, 2013; South East Melbourne Medicare Local [SEMML], 2015).…”
Section: Painmentioning
confidence: 99%